Modelling the dispersion of benzene emissions from a proposed ethanol producing facility in Farewell-Oshawa of Toronto, Canada - Abdul-Wahab, S. A.; En, S. C. F.; Jaffeer, H.; Elkamel, A.; Yetilmezsoy, K.; Ahmadi, L. (GLOBAL NETWORK ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2017)
The production and use of biofuels such as ethanol have been the target of intensive research. One source of ethanol is corn, which is abundant in many countries. In producing ethanol from corn, an assessment of the environmental impact of the process is needed. This study intends to provide insight into benzene emitted from a proposed biofuel plant, its dispersion behavior, and the effects it may have on the immediate environment. Three-season (January, April, and June) dispersion results of benzene emissions from the proposed ethanol-producing facility are evaluated by using the CALPUFF modelling system. Within the framework of the CALPro software, ambient benzene concentrations are modelled over a 24-hour period of exposure by considering the impact of pollutant transformation and removal, and meteorological factors such as wind direction and speed, and temperature. Simulations are performed for the plant area located in Farewell, Oshawa, Ontario, based on the emission and meteorological dataset for the year 2013. The modeling domain covers the area of 30 x 30 km(2) with the grid spacing of 150 m. The number of grid lines is taken as 200 for each axis, and the dispersion of benzene emissions is simulated in nine vertical layers of the domain of study. Based on simulated one-hour and 24-hour average benzene concentrations, pollution dispersion results show that the maximum concentrations are recorded as 4.585 and 0.403 mu g/m(3) at 17h00 LST on hourly basis and on 24-hour basis, respectively, for the winter season. For the spring season, the highest concentrations are measured as 1.345 and 0.136 mu g/m(3) at 21h00 LST for one-hour and 24-hour periods, respectively. For the summer season, the peak benzene concentrations are found to be 1.085 and 0.277 mu g/m(3) at 01h00 LST. The results indicate that none of the months exceeds the half-hour limit of 7 mu g/m(3) set by Ontario Regulation 419/05, but they surpass the Ontario Regulation 419 Schedule 3 limit of 0.01 mu g/m(3) for a 24-hour dispersion period. This information may prove invaluable to further research on the impacts of the ethanol-production process on the environment.
Keywords: Benzene; corn; dispersion; ethanol producing facility; modelling; CARCINOGENS; Environmental Sciences & Ecology